Elaborar un modelo de gestión turístico para el cantón Pujili de la provincia de Cotopaxi. - Moreira Espinoza, Juan Alexander (2017)
Due to the importance that tourism for our country and as a fundamental axis for the economy, the Government has prioritized as public policy the development of tourism through the adequate conservation of resources, promoting the promotion of more competitive markets both to national and international and the involvement of the population sector for the articulation of the tourist system, in addition Ecuador has innumerable zones considered as tourist attractions, the degree of importance of tourism leads to the creation of the Tourism Management Model for the Pujilí canton, which is development oriented with an adequate management and is distributed in four stages; in first stage it is composed of situational diagnostics that allows knowing the reality of the sector, such as its general components, demographic, economic, social and tourist activity, the second stage is the inventory of tourist attractions resulting in 12 attractive inventories and hierarchical which allowed to determine the potential that counts the canton, the third stage is Tourism Management model is based on an integral model based on analysis and defined criteria, is structured with a normative framework, administrative aspects to have a more entrepreneurial business philosophy, Marketing mix, strategies to generate development, programs and projects for the strengthening of tourism, a SWOT analysis to determine internal and external aspects, the fourth stage the draft ordinance has a theoretical framework of ordinance, a Constitutional and normative framework in reference to tourism at cantonal and provincial level, relevant articles of Código Orgánico de Organización Territorial, Autonomía y Descentralización (COOTAD), involved with chapters, articles and for its approval will have general, transitional provisions. In this way the research will serve as a tool for tourism planning and management.